Standardization and adaptation of international advertising. Special emphasis on print advertising in Poland - Korpivaara, Anna (My University, 2006)
This thesis examines standardization and adaptation of print advertising and tries to clarify the present paralleled use of advertising standardization and adaptation. The elements of culture, the characteristics of print advertising and Poland as a country of interest form the frame of reference to be adjusted in the actual substance part of the study where chosen advertisements from Poland, Finland and UK are analysed. Elements of culture are discussed first more generally, and then focus is drawn to the Polish culture. The views behind the phenomenon of standardization and adaptation are presented. Characteristics of advertising such as advertising tradition and style in Poland are discussed. Method of analysis is qualitative/quantitative content analysis. Data is collected from Polish, Finnish and British magazines. Advertisements are classified as to whether they are standardized or adapted. More precisely, to examine the advertisements, Koudelova et al.´s typology (2001) and Whitelock et al.´s Model for Testing Advertising Standardization (1989) are used in this study to examine the executional strategies used in advertisements. The results of this thesis show that drama is the most common format and scenic beauty the most common visual background in the Polish advertisements. Humour is used in ¼ and sex in over half of the Polish advertisements. Polish is the main language in Polish advertisements. The results also show that only one of the Polish advertisements was totally standardized. The rest of the advertisements were either partly or totally adapted.
Keywords: Advertising; standardization; adaptation; culture; Poland; fi=Markkinointi|en=Marketing|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|